The bioscience revolution & the biological weapons threat: levers & interventions - Martin Greg; D'Agostino Mark (BMC, 2009)
Abstract In December 2008, the US Commission on the Prevention of Weapons of Mass Destruction Proliferation and Terrorism, released a report, World At Risk. The Report points to the fact that, not only is the use of a weapon of mass destruction in a terrorist attack before the end of 2013, more likely than not, but also to the fact that terrorists are more likely to be able to obtain and use biological weapons than nuclear. This paper examines the recommendations of the report in the context of the historic and geopolitical changes, in particular globalization. The authors highlight the "dual-use" dilemma, as described in the report, as the paradoxical use of technology developed for the benefit of mankind being used for sinister purposes. The mitigation of such a threat lies in broad stakeholder involvement and cooperation, including non-state actors, governments and the bio-tech industry itself. The importance of vigilance measures within the life science community is emphasized and, the authors propose, could include a web-based didactic course in bioterrorism and weapons of mass destruction identification. The site could outline safety protocols, have detailed disaster management tutorials, and could be specifically tailored for different subsets of industry and health professionals. The paper concludes with an endorsement of a multi-pronged approach including strong international guidelines and intelligence cooperation and preparatory measures such as the wide-spread use of detection systems as well as diagnostic decision support systems for bioterrorism detection at the local level.